Using Windows 3.0, 3.1 effectively - Ross, Paul W.; Ross, Paul Whitcomb (Dubuque : Wm. C. Brown, 1993)
This book is intended for many different kinds of computer users. It is intended primarily to act as a supplementary text in any course using Windows 3.1.
Chapter 1- A review of DOS concepts -- Chapter 2- Installing and starting Windows 3.1 -- Chapter 3- The mouse and the Windows interface -- Chapter 4- Essential Windows skills -- Chapter 5-The file manager -- Chapter 6- Printers and the print manager -- Chapter 7- Customizing with Windows control panel -- Chapter 8- Running applications under Window 3.1 -- Chapter 9- Windows desktop accessories-an overview -- Chapter 10- Windows write -- Chapter 11- Paintbrush -- Chapter 12- Windows terminal -- Chapter 13- Alternative modes of operation -- Chapter 14-Customizing the Windows environment -- Index.
Includes index.
Keywords: MICROSOFT WINDOWS (COMPUTER FILE)